Concomitant Bifocal Urothelial Carcinoma and Breast Tumor: Second Primary Cancer or Metastatic Spread to the Breast? - Clément Dumont; Hélène Gauthier; Jérôme Vérine; Jacqueline Lehmann-Che; Patricia de Cremoux; Damien Pouessel; Stéphane Culine (Case Reports in Oncological Medicine)
Metastases to the mammary gland are an uncommon event in the natural history of most malignant tumors. We report the case of a 60-year-old woman who presented initially with bifocal urothelial carcinoma with a single breast tumor, raising the issue of a primary cancer or a metastatic spread to the breast. The diagnosis of breast metastasis was aided by identity of pathology, immunochemistry, and molecular biology findings between the primary tumor and the breast lesion, among which are the p.K120M mutation, a very rare TP53 mutation, and HER2 overexpression with underlying polysomy of chromosome 17.